NAD(P)-dependent steroid dehydrogenase-like is involved in breast cancer cell growth and metastasis - So-Hyun Yoon; Hoe Suk Kim; Ryong Nam Kim; So-Youn Jung; Bok Sil Hong; Eun Ji Kang; Han-Byoel Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han (BMC Cancer, 2020)
Abstract Background The cholesterol biosynthesis pathway is typically upregulated in breast cancer. The role of NAD(P)-dependent steroid dehydrogenase-like (NSDHL) gene, which is involved in cholesterol biosynthesis, in breast cancer remains unknown. This study aimed to uncover the role of NSDHL in the growth and metastasis of breast cancer. Methods After NSDHL knockdown by transfection of short interfering RNA into human breast cancer cell lines (MCF-7, MDA-MB-231 and BT-20) and human breast epithelial cell line (MCF10A), cell proliferation assay, cell cycle analysis, three-dimensional cell culture, clonogenic assay, transwell migration and invasion assays, and wound healing assay were performed. Erlotinib was used as the target drug for epidermal growth factor receptor. Immunodeficient mice (NOD.Cg-Prkdcscid Il2rgtm1wjl /SzJ) were used as orthotropic breast tumor models by injecting them with NSDHL-knockdown MDA-MB-231 cells using lentivirus-carrying NSDHL short hairpin RNA. Clinical data from 3951 breast cancer patients in Gene Expression Omnibus databases were used to investigate the potential prognostic role of NSDHL by survival analysis. Results NSDHL knockdown in BT-20, and MDA-MB-231 resulted in a significant decrease in their viability, colony formation, migration, and invasion abilities (p < 0.05). Total cholesterol levels were observed to be significantly decreased in NSDHL-knockdown BT-20 and MDA-MB-231 (p < 0.0001). NSDHL knockdown significantly increased the rate of erlotinib-induced cell death, especially in MDA-MB-231 (p = 0.01). NSDHL knockdown led to significantly decreased tumor growth and lung metastasis in the MDA-MB-231 xenograft model (p < 0.01). Clinically, high NSDHL expression in tumors of patients with breast cancer was associated with significantly reduced recurrence-free survival (p < 0.0001). Conclusions NSDHL might have a role in promoting breast cancer progression. The usage of NSDHL as a therapeutic target in breast cancer needs to be clarified in further studies.